2002
DOI: 10.1292/jvms.64.607
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Toxic Metals and Essential Minerals in the Mane Hair of Healthy Racing Horses and Their Relation to Age.

Abstract: ABSTRACT. Concentrations of trace elements (As, Al, Pb, Cd, Hg, Se, Si, P, Na, K, Ca, Mg, Fe, Cu, Zn, Mn, Cr, Ni and Mn) in the mane hair obtained from 9 female and 15 male healthy racing Thoroughbred horses aged 2-5 years were analyzed by the inductively coupled plasma atomic emission spectrometry (ICP-AES) method. No significant differences between the female and male horses were observ ed in the mean concentrations of those minerals. Significantly positive correlations with age were observed in Cd (r=0.546,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 14 publications
4
43
3
1
Order By: Relevance
“…On the other hand, the mean results found in this study were higher than those obtained by Bianu (2004) in horses from polluted areas in Romania (47.5-53.5 µg g -1 ), by Asano et al (2002), in 24 Japanese healthy racing horses (86±24 μg g -1 ), and by Farmer and Farmer (2000), for horses raised around a metal production center in eastern Kazakhstan (112.70±6.29 µg g -1 ). Pourjafar et al (2008) showed association between contamination and hair Pb presence, after evidence of negative relationship between hair Pb contents and distance from pollution source in Iran.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…On the other hand, the mean results found in this study were higher than those obtained by Bianu (2004) in horses from polluted areas in Romania (47.5-53.5 µg g -1 ), by Asano et al (2002), in 24 Japanese healthy racing horses (86±24 μg g -1 ), and by Farmer and Farmer (2000), for horses raised around a metal production center in eastern Kazakhstan (112.70±6.29 µg g -1 ). Pourjafar et al (2008) showed association between contamination and hair Pb presence, after evidence of negative relationship between hair Pb contents and distance from pollution source in Iran.…”
Section: Discussioncontrasting
confidence: 81%
“…The hair Cu mean contents obtained in this study were close to the 4.8±1.3 μg g -1 obtained by Asano et al (2002) for the hair of 24 healthy thoroughbred racing horses from Japan, and slightly lower than the 7.3±1.7 μg g -1 , observed by Wichert et al (2002) for 106 horses from Germany. The authors from those studies indicated their values as reference to healthy animals or very similar to data previously reported from horses without clinical signs of contamination, or even as associated with normal range.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These elements were selected since their presence in large quantities in the water may be harmful to the animals' health (Fernández Cirelli et al, 2010;Asano et al 2002); besides, in Argentina, arsenic is a toxic natural element very often found in ground and surface water (Smedley & Kinninburgh 2002). This element comes from the pampean loess and it is present in large quantities in the ground and surface water of the Pampas plains (Farías et al 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Na continuação, foram realizadas lavagens com água Milli-Q e duas lavagens com acetona P.A., sendo as amostras deixadas secar em temperatura ambiente. Por fim, as amostras foram secas em chapa aquecedora a 70 o C (ASANO et al, 2002). A digestão das amostras de pelo foi efetuada de acordo com a técnica descrita por PIMENTA & VITAL (1994), na qual 0,4g do material foi solubilizado em 10mL de ácido nítrico concentrado em chapa aquecedora.…”
Section: Methodsunclassified